Genetic composition of Kazakh horses of Zhabe type evaluated by SNP genotyping - Alexandr Pozharskiy; Indira Beishova; Askar Nametov; Alzhan Shamshidin; Tatyana Ulyanova; Alexandr Kovalchuk; Vadim Ulyanov; Malika Shamekova; Gulmira Bekova; Dilyara Gritsenko (Heliyon)
Horses are animals traditionally playing prominent role as both food source and working animals for Kazakh people. Zhabe horses are traditional type of indigenous Kazakh horses characterized by versatility and adaptation to conditions of Central Asia. The present work focuses on examination of genetic structure of Zhabe horses using SNP genotyping with addition of previously published data. Total 1038 individuals including 403 new samples of Zhabe horses and 42 sample of white horses ‘Zhetysu Asyly’ have been considered. DNA was extracted from hair roots using commercial DNA isolation kit and further used for analysis of SNP by Illumina iScan system with Equine80k SNP array. The analysis of population genetic parameters (expected and observed heterozygosity, linkage disequilibrium, Wright's Fst) and genetic structure (PCA, ADMIXTURE) in comparison with publicly available data on selected foreign cultivars demonstrated low between population differentiations and lack of selection factors. Genome wide association study performed for body size and weight have revealed low occurrence of SNPs with significant associations, total 57 SNPs linked to various genes with low density across all genome. The obtained results highlight difference between traditional horse breeding practices of Kazakh people and stable based breeding of foreign breeds. In contrast, the ‘Zhetysu Asyly’ horse breed derived from Kazakh horses demonstrate the effect of intense breeding process on the same landrace. The results provide new data on the traditional Kazakh horses of type Zhabe and will assist further studies of this original landrace.